STRATEGI PENGORGANISASIAN LEMBAGA KESEHATAN NAHDLATUL ULAMA (LKNU) DALAM PENGELOLAAN PROGRAM HIV/AIDS (Studi Kasus Pengelolaan Dana Hibah Global Fund AIDS di Indonesia) - Henri Puteranto (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
The problems of managing HIV/AIDS programs arises when religious social organizations run the program. Religious organizations are required to run the program effectively. However, the implementation is not easy since they have to faced the “body of knowledge” of HIV/AIDS programs. Therefore, the ability of the organization to undertake this program is crucial. Religious organizations have a role to still keep the significance of religious values, at the same time to avoid conflct with the strategies possessed in HIV programs. This study explores three issues in the Health Organization of Nahdlatul Ulama, the interaction of values and norms, efforts to establish the organization legitimacy, and the ability to perform knowledge management. Qualitative research methods is used to explore the three issues mentioned above. The study results showed that the Health Organization of Nahdlatul Ulama as a socioreligious organization is able to answer sensitive issues in HIV/AIDS programs to reduce stigma and discrimination, building of organization legitimacy and conducting of knowledge management effectively